2004
DOI: 10.1542/peds.113.6.1636
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous Bilirubin Measurements and Serum Total Bilirubin Levels in Indigenous African Infants

Abstract: From these results, we can conclude that TcB measurements are a useful and reliable index for estimating STB levels in pigmented neonates, including those with hyperbilirubinemia and kernicterus. In the absence of reliable STB measurements, the relatively simple and noninvasive TcB measurements can be an important adjunct in directing phototherapy and exchange transfusions, thereby preventing bilirubin-induced morbidity and mortality in low-technology clinical environments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
2
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(52 citation statements)
references
References 17 publications
5
43
2
1
Order By: Relevance
“…Skin color was classified as previously reported in this population, 14 and recorded by the trained nurse assistants as shown in a color guide (Supplemental Fig 5). G6PD evaluation was based on the fluorescent blood spot for all infants by using methods described by Beutler et al, 17 as previously reported.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Skin color was classified as previously reported in this population, 14 and recorded by the trained nurse assistants as shown in a color guide (Supplemental Fig 5). G6PD evaluation was based on the fluorescent blood spot for all infants by using methods described by Beutler et al, 17 as previously reported.…”
Section: Methodsmentioning
confidence: 99%
“…9, 10, 14, 15, 21 -23 The TSB overestimation is also corroborated by several studies among multiracial populations 10,13,24 and black neonates. 14,15 For example, although Maisels et al 10 found a close correlation between TcB and TSB values among 849 neonates across all ethnic groups, by using JM-103, TSB was overestimated by ≥2 mg/ dL in 37.9% of blacks, compared with 1.8% of whites or 5.4% of other races. Among black infants, TSB was overestimated by ≥3 mg/dL in 17.4% and by ≥4 mg/dL in 6.7%.…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
See 2 more Smart Citations
“…Extreme hyperbilirubinaemia is uncommon in developed countries. It is still a common cause of neonatal morbidity and mortality in developing countries often resulting in kernicterus with its resultant burden, such as medical, economic and social, on the patient family and society at large 3 .…”
Section: Imentioning
confidence: 99%